Neuroendocrine Tumours Diagnosis and Management - Yalcin, Suayib.; Yalcin, Suayib.; Öberg, Kjell.; Öberg, Kjell. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book is a timely textbook that covers all aspects of neuroendocrine tumors (NET) from epidemiology, pathological classification and evaluation, and molecular biology through to diagnostic imaging methods and therapeutic options, including the latest targeted therapies. The various types of NET are individually discussed, including carcinoid tumors, insulinomas, gastrinomas, glucagonomas, VIPomas, somatostatinomas, PPomas, medullary thyroid carcinomas, adrenocortical cancer, pheochromocytomas, paragangliomas, and non-functioning pancreatic NETs.  The contributing authors are internationally recognized experts who bring a wealth of experience to the subject. This book will be an invaluable source of information for practicing medical oncologists, surgeons, endocrinologists, gastroenterologists, and pathologists and also trainees.  .